Highlighting Grammatical Errors By Using Writing Journal to Improve Writing Accuracy - Sari, Retma (UPA Bahasa Universitas Tidar And HISKI Kedu, 2021)
Errors and mistakes in foreign language use is the reflection of learners’ language learning process. Learners can profit from their errors if appropriate feedback is provided after errors or mistakes have committed by learners. Even in modern times errors have not been tolerated in language classrooms and seen as a deficiency in language use. However, according to important scholars errors present a view which is related with learners’ discovery of a foreign language. Within the light of this perspective the current research aimed to analyze the grammatical problem and overcome the problem with writing journal. Besides, this study investigated grammatical problems and its solution, the participants were third years students of English department. They The researcher proposes, in this paper, the action research with a quasi quantitative and qualitative design, to provide some important insights into the use of journal writing as a means to improve grammatical accuracy with no prior exposure to journal writing in English. The data on the undergraduates’ grammatical accuracy will be analyzed through their journal entries covering both dialogue-journaling and process-writing entries, while their opinions of journal entries and grammatical accuracy were obtained through their dialogue journaling entries and interview responses. Findings are discussed, and recommendations for future research are made. It is also hoped that journal writing can be another useful learning activity and a teaching alternative to enhance EFL undergraduates’ grammatical accuracy.